PENGEMBANGAN MEDIA BERBASIS KOMPUTER UNTUK PEMBELAJARAN KIMIA KELAS XI PADA SEKOLAH MENENGAH ATAS - Berlina, Berlina; Wiryotinoyo, Mujiyono; Muhammad, Damris (Program Magister Teknologi Pendidikan Universitas Jambi, 2014)
Difficulty learning abstract consepts in material forms of the molecule based on the theory of electron domain and molecular hybridization in the formation of simple covalent coumpounds involving electron is verry small in size. With conventional learning to use the media shaped balloons and images/charta make their experience misconceptions. Make use of computer assisted animations media adobeflash program. The program is able to help students discover and explore the concepts of learning materials to animate the process of formation of the molecules of the compound geometry. The program is easy to obtain and can be used on all computers. Material forms of molecules according to VSEPR theory (valence shell electron pair repulsion) and Hybridization theory contained in the computer based media is aimed at helping students learn to achieve mastery of core competencies which are already contained in the syllabus set by time. Products are developed in accordance with the educational technology area abstract include students in determining the geometry of the steps forming the molecules of the compound. The stages are carried out in the development of media, namely: design learning, create computer based animation media, validate products with product testing. Advice of expert material/content, media expert, design expert, and data from trials of the target group to be enter performance improvement products. Based on the results of the expert validation and testing of the target group can be concluded that the computer –based instructional media products on the molecular forms of material at Senior High School chemistry in particular at ninth grade IPA (Natural Sciences). With regard to these results the school, especially Senior High School 8 Batanghari media products in order to incorporate this learning into the school website that can be accessed by the wider media users for further development. Keyword: Development, Computer based Media, Molecular Forms.